2015
DOI: 10.14810/ijmech.2015.4107
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dam Location on the Performance Characteristics of Two -Lobe Bearing: Micropolar Lubricated

Abstract: This paper presents the effect of pressure dam parameters on the static and dynamic characteristics of two lobe pressure dam bearing. The modified Reynolds equation is derived on the basis of micropolar fluid theory. The Galerkin approach of finite element method has been used to solve modified Reynold's equation for carrying out the performance characteristics. The characteristics, which have been calculated for a wide range of dam parameters, have been found to be greatly influenced with the variation of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
(15 reference statements)
0
1
0
Order By: Relevance
“…Dwivedi et al 8 studied the impact of geometry of lobes and L/D ratio on the static characteristics of two-lobe journal bearing. Sharma and Krishna 9 evaluated the performance of two-lobe pressure dam bearings operating under micropolar fluid. They demonstrated that the stability of two-lobe pressure dam bearings increased with the decrease of aspect ratio ( L / D ).…”
Section: Introductionmentioning
confidence: 99%
“…Dwivedi et al 8 studied the impact of geometry of lobes and L/D ratio on the static characteristics of two-lobe journal bearing. Sharma and Krishna 9 evaluated the performance of two-lobe pressure dam bearings operating under micropolar fluid. They demonstrated that the stability of two-lobe pressure dam bearings increased with the decrease of aspect ratio ( L / D ).…”
Section: Introductionmentioning
confidence: 99%